Evaluation of the Xpert® MTB/RIF assay and microscopy for the diagnosis of Mycobacterium tuberculosis in Namibia. Issue 1 (December 2017) - Mavenyengwa, Rooyen; Shaduka, Emma; Maposa, Innocent
Abstract Background Tuberculosis (TB) kills approximately two million people and infects around nine million worldwide annually. Its proper management, especially in resource-limited settings, has been hindered by the lack of rapid and easy-to-use diagnostic tests. Sputum smear microscopy remains the cheapest, readily available diagnostic method but it only identifies less than half of the patients with a HIV/TB co-infection because the bacilli would have disseminated from the lungs to other areas of the body. The fully automated Xpert® MTB/RIF assay is a promising innovation for diagnosing TB and detecting resistance to rifampicin. This study aimed to evaluate the use of Xpert® MTB/RIF assay and microscopy in the diagnosis ofMycobacterium tuberculosis in Namibia, by determining the disease's epidemiology and calculating the proportion of cases infected just with TB and those with a resistance to rifampicin among the total suspected cases of TB in the country. Methods This retrospective study analysed TB cases that were diagnosed using both the Xpert® MTB/RIF assay and microscopy. Data were collected from patient records from the Meditech laboratory information system of the Namibia Institute of Pathology for the time period of July 2012–April 2013. Data from 13 regions were collected. Results The total number of specimens collected from patients with symptoms of pulmonary TB was 1 842. Of these, 594 (32.20%) were found to be positive for MTB by Xpert® MTB/RIF assay, out of which 443 (24.05%) were also found to be positive by microscopy. The remainder was negative. The male patients were more resistant to rifampicin when compared to the female patients. Conclusions Tuberculosis is widely distributed throughout Namibia, with slightly more males infected than females. Most TB patients are also co-infected with HIV. Both microscopy and Xpert® MTB/RIF assay are crucial for the diagnosis of TB in the country. Screening diagnostic efforts should focus on the sexually active HIV positive male population who could be the source of more RIF-resistant TB than females to prevent its spread.